AB0206 IS DISEASE SEVERITY A RISK FACTOR FOR CARDIOVASCULAR MORTALITY IN INFLAMMATORY MYOSITIS? ANALYSIS OF THE REGISTRY OF INFLAMMATORY MYOSITIS FROM THE MADRID COMMUNITY (REMICAM). (June 2019) - Joven-Ibáñez, Beatriz; Nuño, Laura; López-Longo, Francisco J.; Martinez-Barrio, Julia; Larena, Carmen; Maldonado, Valentina; Barbadillo, Carmen; Peña, Paloma García de la; Llorente, Irene; Muriel, Eva Tomero; Gómez, Ana Pérez; Moruno, Henry; et al.
Abstract : Background: Inflammatory myositis (IM) are heterogeneous autoimmune diseases, characterized by muscular inflammation, which can associate systemic manifestations. In other inflammatory diseases, as rheumatoid arthritis, inflammation is a cardiovascular risk factor (CVRF), with clear influence on cardiovascular events and mortality (CVE, CVM). Objectives: To analyze the influence of IM severity in the development of CVE and CVM in the REMICAM registry. Methods: All patients from REMICAM were included(1). REMICAM is a retrospective multicentric registry of IM patients (n=479), performed in Madrid between 2012 and 2014, containing demographic, clinical and outcome data (1). The presence of extra muscular features (cardiac, pulmonary, cutaneous and systemic involvement), number of therapies, immunosuppressants (IS) need, and glucocorticoids (GC) withdrawal due to IM remission defined IM severity. Bi and multivariate logistic regression analysis were used to determine the association between these factors and CVE. Survival analysis and regression proportional hazard bi and multivariate Cox models were used to determine the effect of these factors on CVM. All factors with p< 0, 2 in bivariate analysis were included in multivariate models. The effect was controlled for age, sex and CVRF. Results: From 479 patients (74% females, 52% polymyositis, 44±22 years at diagnosis, 10±8 years follow up), 104/467 (22%) presented CVE and 24/409 (6%) died due to CVE. CVE were associated to age, male sex, CVRF number, diagnosis before year 2000, presence of arrhythmia or Raynaud (Table 1 ). Arrhythmia was the only independent risk factor for CVM. GC withdrawal due to IM remission, and a smaller number of therapies, were protective factors for CVM (Table 2 ). Conclusion: In the REMICAM registry, extra muscular manifestations such as arrhythmia, were associated to CVE and CVM, as independent risk factors. A smaller number of treatment or GC withdrawal due to remission were protective factors for CVM. Our results support the hypothesis that more severe IM, with extra muscular involvement and persistent inflammation, could favor atherosclerosis and CVE development. Reference: [1] Nuño L, Rheumatol Clin2017; 13:331-337 Disclosure of Interests: Beatriz Joven-Ibáñez Speakers bureau: Celgene, Novartis, MSD, Pfizer, AbbVie, and Janssen, Laura Nuño: None declared, Francisco J López-Longo: None declared, Julia Martinez-Barrio: None declared, Carmen Larena: None declared, Valentina Maldonado : None declared, Carmen Barbadillo: None declared, Paloma García de la Peña: None declared, Irene Llorente : None declared, Eva Tomero Muriel: None declared, Ana Pérez Gómez: None declared, Henry Moruno : None declared, Tatiana Cobo-Ibáñez: None declared, RAQUEL ALMODOVAR: None declared, LETICIA LOJO : None declared, María Jesús García de Yébenes: None declared, Patricia Carreira: None declared